RE-INVENTING THE ROLE OF FEMALEULAMA IN THE INTELLECTUAL TRADITION OF ISLAM MALAY - Abdul Mujib (Ri'ayah: Jurnal Sosial dan Keagamaan, 2019)
Studies on the involvement of female ulama (Muslim clerics) in the Islamic intellectual tradition are still in quite small number, not only in Malay-Nusantara area, but also in other Muslim regions such as Arabia, West Asia, Africa, North Africa, subcontinent of India, and so forth. Even though the studies on woman and gender is recently getting their momentum, the focused attention is not referred to the socio-cultural history of female ulama. This paper is a library research in nature. It attempts to deeply present the role of Fathimahbinti Abdul WahabBugis in the intellectual tradition of Islam Malay. It is concluded that Fathima’s role is very significantly considered in the intellectual tradition particularly in the field of fiqh (jurispundence).